Java elearning kit for dummies - Mueller, John Paul. (Wiley Pub., Inc., 2012)
Learn how to analyze and display data that makes an impact! This guide helps you explore common types of data visualization, shows you good and bad applications, and helps you use your data to give you a competitive edge.